Modern Approach in Treatment of Diabetes Insipidus (Biomolecules and Biomedicine, 2005)
In this paper we have reviewed the possition of desmopressin in the treatment of diabetes insipidus. Desmopressin is a synthetic analog of vasopressin, with more pronounced antidiuretic effect. It is treatment of choice in substitution therapy of diabetes insipidus. Its application before sleeping time can reduce nocturnal enuresis, so it has a place in the treatment of enuresis nocturna. Antidiuretic effect of desmopressin is the result of agonistic effect on V2 receptors in the renal tubules. The efficacy and safety of desmopressin in mentioned indications was confirmed in clinical studies.